Library in virtual reality - An innovative way for accessing, disseminating, and sharing information - Kirner, Tereza G.; Matos, Andrea T.; Costa, Placida L. [UNESP]; INSTICC (Insticc-inst Syst Technologies Information Control & Communication, 2006)
This paper focuses on Virtual Reality (VR) as a very powerful technology that can be applied to the libraries, aiming at contributing to the activities of accessing, disseminating, and sharing information. The paper presents the VR concept and describes some libraries in virtual reality under utilization in different countries. In the final considerations, it is pointed out the use of virtual reality to develop libraries as collaborative virtual environments.
Keywords: digital libraries; virtual reality